2010
DOI: 10.1111/j.1365-2486.2010.02178.x
|View full text |Cite
|
Sign up to set email alerts
|

Production and fitness of Fusarium pseudograminearum inoculum at elevated carbon dioxide in FACE

Abstract: Rising atmospheric carbon dioxide (CO 2 ) concentration is increasingly affecting food production but how plant diseases will influence production and quality of food under rising CO 2 is not well understood. With increased plant biomass at high CO 2 the stubble-borne fungal pathogen Fusarium pseudograminearum causing crown rot (CR) of wheat may become more severe. We have studied inoculum production by Fusarium using fungal biomass per unit wheat stubble, stem browning from CR and the saprophytic fitness of F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
97
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(98 citation statements)
references
References 55 publications
1
97
0
Order By: Relevance
“…In Mv Regiment, which was the least susceptible variety, a similar rate of infection was observed at both ambient and elevated CO 2 levels. The variation found here between wheat varieties was in accordance with previous results reported by Melloy et al (2010) on Fusarium pseudograminearum, which causes wheat crown rot. These authors found increased fungal biomass and/or increased stem browning in response to EC in some situations, which exhibited variety dependence.…”
Section: Discussionsupporting
confidence: 82%
“…In Mv Regiment, which was the least susceptible variety, a similar rate of infection was observed at both ambient and elevated CO 2 levels. The variation found here between wheat varieties was in accordance with previous results reported by Melloy et al (2010) on Fusarium pseudograminearum, which causes wheat crown rot. These authors found increased fungal biomass and/or increased stem browning in response to EC in some situations, which exhibited variety dependence.…”
Section: Discussionsupporting
confidence: 82%
“…In South Asia, spot blotch in wheat (Cochliobolus sativus) has increased substantially in recent years and it is speculated that elevated night temperatures due to climate change has contributed to this (Sharma et al, 2007). In Australia, root and crown rot of wheat (Fusarium pseudograminearum) is expected to increase due to climate change as the disease was high with elevated CO 2 , temperature, and drought (Melloy et al, 2010). There is no information available on the impact of climate change on the dynamics of mungbean diseases.…”
Section: Economic Impact Of Mungbean Fungal Diseasesmentioning
confidence: 99%
“…Several soil-borne pathogens, such as Rhizoctonia, Fusarium etc. are common problem in rice and wheat (Kobayashi et al, 2006;Melloy et al, 2010). These fungal genera also infect mungbean, but more studies are required to determine if the same species and strains also infect mungbean.…”
Section: Cultural and Physical Practicesmentioning
confidence: 99%
“…Changes in plant physiology at high CO 2 concentrations influence the life cycle of insect pests, weeds, and plant pathogens. The fecundity of many biotrophic (Hibberd et al 1996) and necrotrophic (Melloy et al 2010) pathogens increases at elevated CO 2 . The enlarged crop canopy from a CO 2 fertilisation effect increases the number of infection cycles to further boost pathogen population, potentially increasing the rate of evolution of new races (Chakraborty and Datta 2003).…”
Section: Adaptation To New Pests and Pathogensmentioning
confidence: 99%